Tinjauan Yuridis Dalam Peredaran Uang Palsu Di Kota Makassar Analisis Putusan No. 863/Pid.B/2020/Pn.Mks - Risman; Asrul Aswar; Syahrul Akbar (Pledoi Law Jurnal, 2025)
ABSTRACT: With the development of science and technology, crimes such as the distribution of counterfeit money have become easier to commit. Counterfeiting money triggers various crimes, including terrorism, political crimes, and money laundering. This research focuses on the causal factors of counterfeit money distribution and the sanctions imposed on perpetrators. The causal factors include endogenous factors, such as individual characteristics (age 15-25 years, education level, religious beliefs), and exogenous factors, such as family and social environment. Disharmonious families and poor social environments, as well as difficult economic conditions and technological advances, increase the risk of this crime. Perpetrators of counterfeit money distribution are subject to severe sanctions under Law No. 7/2011, which carries a penalty of up to 15 years in prison and a fine of 50 billion rupiah. ABSTRAK: Seiring perkembangan ilmu pengetahuan dan teknologi, kejahatan seperti penyebaran uang palsu semakin mudah dilakukan. Pemalsuan uang memicu berbagai kejahatan, termasuk terorisme, kejahatan politik, dan pencucian uang. Penelitian ini berfokus pada faktor penyebab kejahatan pengedaran uang palsu dan sanksi yang dijatuhkan kepada pelakunya. Faktor penyebabnya meliputi faktor endogen, seperti karakteristik individu (usia 15-25 tahun, tingkat pendidikan, kepercayaan agama), serta faktor eksogen, seperti lingkungan keluarga dan pergaulan. Keluarga yang tidak harmonis dan lingkungan sosial yang buruk, serta kondisi ekonomi sulit dan kemajuan teknologi, turut meningkatkan risiko kejahatan ini. Pelaku pengedaran uang palsu dikenai sanksi berat berdasarkan UU No. 7 Tahun 2011, dengan ancaman pidana hingga 15 tahun penjara dan denda 50 miliar rupiah.